Association between hyperglycemia and unfavorable outcome in patients with successful thrombectomy for acute ischemic stroke: a single-center study - Ao Qian; Longyi Zheng; Shuang Tang; Wenli Xing (BMC Neurology)
Abstract Purpose The aim of this study was to evaluate the associations between hyperglycemia, dynamics of glucose levels and unfavorable outcome in acute ischemic stroke (AIS) patients undergoing mechanical thrombectomy (MT). Methods A retrospective study was conducted in our center. Blood glucose levels were measured at admission, immediately following MT procedure, and under fasting condition the next morning. Two patterns of blood glucose increase (BGI) were defined: postoperative BGI as higher postoperative blood glucose level than the value at admission, and fasting BGI as fasting blood glucose level exceeding the value at admission. Hyperglycemia was classified as any blood glucose measurements ≥ 8 mmol/L. Unfavorable outcome was defined as a modified Rankin Scale (mRS) score > 2 at 90 days after onset. Multivariable logistic regression was performed to assess the associations of blood glucose levels at three time points (admission, postoperative, and the next-morning fasting), BGI, and unfavorable outcome. Lastly, mediation analysis was conducted to assess the potential mediating role of systemic inflammatory response in the association between hyperglycemia and unfavorable outcome. Results A total of 395 patients were enrolled, and 224 (56.7%) experienced unfavorable outcome. After multivariable adjustment, admission (adjusted odds ratio [aOR] 4.030, 95% CI 2.200-7.382), postoperative (aOR 2.462, 95% CI 1.354–4.476), and fasting hyperglycemia (aOR 4.309, 95% CI 2.271–8.176) were independently associated with unfavorable outcome. Moreover, fasting BGI was also found as a significant risk factor for unfavorable outcome (aOR 2.077, 95% CI 1.167–3.696). The relationships of admission and fasting hyperglycemia with unfavorable outcome were mediated by systemic inflammation markers, with mediation proportions ranging from 10.4 to 21.8% (all p < 0.05). Conclusion Our findings support hyperglycemia and fasting BGI indicating elevated risk of unfavorable outcome in AIS patients undergoing MT, with systemic inflammation partially mediating these association.